PERSEPSI MAHASISWA JURUSAN AKUNTANSI TERHADAP PROSES BELAJAR MENGAJAR MATA KULIAH AKUNTANSI PENGANTAR BERDASAR KURIKULUM BERBASIS KOMPENTENSI (KBK). - Rizki Intan Destiana (AKT 15 UMY 191, 2015)
This study aims at examining accounting students perceptions on teaching and learning based on competency-based Curriculum at Accounting Department of the Faculty of Economics Universitasof Muhammadiyah Yogyakarta. The subject of this study is students of accounting department of the faculty of University of Muhammadiyah Yogyakarta economics who have completed the introductory accounting courses. Data collection methods that retrieve data directly through questionnaires to respondents and dept interviews with respondents who have completed the introductory accounting course. The number of samples in this shows were 150 respondents.The results of this study ststes that variable environmental factors have an average total value of the highest percentages of 74, % and variable competence of lectures had an average total value of the lowest percentage that is equal to 64,% These study suggests for improvement of teaching and learning introductory accounting courses at University of Muhammadiyah Yogyakarta, which are in the aspect of learning with friends campus made in the spirit of learning states that the number of group members so that it can more focused on what was discussed and encouraging its members and in the aspect of the KBK better understanding of the material should have a students must be prepared in the implementation of the KBK because the system can encourage students to be more active in the learning process and practice self sufficiency.